Paddy farmers' awareness and knowledge of agroforestry practices in Siburan, Sarawak - Jacklin, Mathew; Daniel Ugih, Echoh; Mohamad Hilmi, Ibrahim (Wiley Periodicals LLC, 2025)
Rice is an important staple food and the main source of income and livelihood, especially for rural communities in Malaysia. However, the area under rice cultivation in Malaysia has decreased due to poor quality of rice fields due to low productivity and climate change. Agroforestry is a system that combines trees with crops or livestock. It not only counteracts the effects of climate change by increasing the resilience of agriculture, but also combats poverty, food security, and land degradation. The aim of this study was to determine the awareness and perception of rice farmers in Siburan, Sarawak, toward agroforestry. The data for the study were obtained through questionnaire-based interviews in Kampung Skuduk and Kampung Chupak. Statistical tests were used to analyze and compare the data. Farmers’ knowledge of agroforestry practices was limited, especially among non-agroforestry practitioners. There is no significant income difference between agroforestry practitioners and non-agroforestry practitioners as agroforestry is practiced on a small scale and for household consumption as there are no commercial market opportunities for the products. Governmental or non-governmental organizations should organize educational activities on agroforestry to disseminate information on these practices appropriate to the education level and age group of the target farmers. Awareness raising and information dissemination activities are important as lack of awareness hinders the implementation of agroforestry, for example, through awareness campaigns and training programs on agroforestry. The results of this study will serve as a guide for the authority to plan measures to increase the knowledge and importance of the agroforestry sector and the implementation of agroforestry.